Atrial natriuretic peptide and leptin interactions in healthy men - Daniels, Martin A.; Fischer-Posovszky, Pamela; Boschmann, Michael; Jumpertz-von Schwartzenberg, Reiner; Müller, Timo D.; Sandforth, Leontine; Frank-Podlech, Sabine; Hülskämper, Sonja; Peter, Andreas; Wabitsch, Martin; Jordan, Jens; Birkenfeld, Andreas L. (Frontiers in Endocrinology, 2023)
Introduction: Atrial natriuretic peptide (ANP), a hormone secreted from the heart, controls cardiovascular and renal functions including arterial blood pressure and natriuresis. ANP also exerts metabolic effects in adipose tissue, liver and skeletal muscle, including secreting adipokines. We tested the hypothesis that ANP lowers concentrations of the anorexigenic adipokine leptin in healthy humans in vivo. Methods: Human ANP or matching placebo was infused intravenously (iv) into healthy men in a randomized, controlled setting. Results: Within 135 minutes of iv ANP infusion, we observed an acute decrease in plasma leptin levels compared to controls. Free fatty acids markedly increased with ANP infusion in vivo, indicating activated lipolysis. In human SGBS adipocytes, ANP suppressed leptin release. Discussion: The study shows that the cardiac hormone ANP reduces the levels of the anorexigenic adipokine leptin in healthy humans, providing further support for ANP as a cardiomyokine in a heart - adipose tissue axis. (registered in the German Clinical Trials Register and the WHO International Clinical Trials Registry Platform was granted under DRKS00024559)